El proceso de enseñanza-aprendizaje y su influencia en el desarrollo del pensamiento crítico – reflexivo de los niños de primer año de educación básica del jardín de infantes Jose Miguel García Moreno de la ciudad de Loja, durante el año lectivo 2012 - 2013”. Lineamientos alternativos - Pérez González, Mónica (2013)
The present investigation was designed to "process education - learning and its influence on the development of critical thinking - reflective of the children in the first year of basic education from kindergarten José Miguel García Moreno in the city of Loja, during the school year 2011 - 2012 " It took into account the overall objective: To examine the approaches applied in the teaching - learning influence the development of critical thinking - reflective of children first year basic education establishment involved. Methods were applied as descriptive, hermeneutical and explanatory analytical, statistical, and for the development of the analysis came to the descriptive method. The techniques applied were: teacher surveys and observation guides for children, which allowed empirical information related to know how to develop critical thinking - reflective in children, the same that was qualitatively analyzed and processed and then confronted with the theoretical. According to the criteria of teachers was learned that the play activity is used as a strategy for the development of critical thinking - reflective of the children, who perform these skills in the teaching - learning and daily activities not all Teachers use the learning cycle activities this thought developers envisioned that we need to insist on this point. Regarding the observation guide applied to children's educational center in terms of skills: IDENTIFICATION, COMPARISON, AND CLASSIFICATION MANAGEMENT it was found that the children have developed these skills mean, ie it takes that in daily practice to include a methodology that is able to develop these thinking skills, through activities and strategies to develop critical thinking - reflective and improve the education of children in this age. Finally it outlines alternative recommendations for Teachers and Garden Kids investigated, in order to ensure quality teaching processes to achieve effective learning and develop critical thinking - reflective as discussed in our day.